Lifting the Veil of Ignorance – Survey Experiments on Preferences for Wealth Redistribution - Elisa Stumpf; Silke Uebelmesser (CESifo GmbH, 2024)
We study beliefs about wealth inequality and preferences for wealth redistribution. For this, we conduct a large-scale online survey in Germany. First, we analyze how well participants are informed about the German wealth distribution and their position in it. Second, we investigate how preferences for wealth redistribution are affected by an information experiment. One treatment group receives information about the shape of the German wealth distribution, while another treatment group receives information about their position in this distribution. Using a multidimensional approach to measure preferences for wealth redistribution, we find no significant average treatment effect for either treatment in the full sample, although those who overestimate their position reduce their aversion to inequality after learning their position, while those who underestimate their position are more likely to agree that anyone can become successful through hard work. We employ a data-driven approach to further investigate heterogeneity in treatment effects and present evidence that younger participants decrease their support for redistribution after learning about the shape of the wealth distribution. In contrast, older participants decrease their support after learning their position in the distribution.
Keywords: C90; D31; D63; D83; 330; wealth distribution; preferences for redistribution; inequality; survey experiment; information provision